Learning from the other limb's experience: sharing the 'trained' M1 representation of the motor sequence knowledge. (23rd November 2015) - Gabitov, Ella; Manor, David; Karni, Avi
Abstract : Key points: Participants were scanned during the untrained‐hand performance of a motor sequence, intensively trained a day earlier, and also a similarly constructed but novel, untrained sequence. The superior performance levels for the trained, compared to the untrained sequence, were associated with a greater magnitude of activity within the primary motor cortex (M1), bilaterally, for the trained sequence. The differential responses in the 'trained' M1, ipsilateral to the untrained hand, were positively correlated with experience‐related differences in the functional connectivity between the 'trained' M1 and (1) its homologue and (2) the dorsal premotor cortex (PMd) within the contralateral hemisphere. No significant correlation was evident between experience‐related differences in M1 – M1 and M1 – PMd connectivity measures. These results suggest that the transfer of sequence‐specific information between the two primary motor cortices is predominantly mediated by excitatory mechanisms driven by the 'trained' M1 via two independent neural pathways. Abstract: Following unimanual training on a novel sequence of movements, sequence‐specific performance may improve overnight not only in the trained hand, but also in the hand afforded no actual physical experience. It is not clear, however, how transfer to the untrained hand is achieved. In the present study, we examined whether and how interaction between the two primary motor cortices contributes to the performance of a sequence of movements, extensively trained the day before, by the untrained hand. Acordingly, we studied participants during the untrained‐hand performance of a finger‐to‐thumb opposition sequence (FOS), intensively trained a day earlier (T‐FOS), and a similarly constructed, but novel, untrained FOS (U‐FOS). Changes in neural signals driven by task performance were assessed using functional magnetic resonance imaging. To minimize potential differences as a result of the rate of sequence execution per se, participants performed both sequences at an identical paced rate. The analyses showed that the superior fluency in executing the T‐FOS compared to the U‐FOS was associated with higher activity within the primary motor cortex (M1), bilaterally, for the T‐FOS. The differential responses in the 'trained' M1 were positively correlated with experience‐related differences in the functional connectivity between the 'trained' M1 and (1) its left homologue and (2) the left dorsal premotor cortex. However, no significant correlation was evident between the changes in connectivity in these two routes. These results suggest that the transfer of sequence‐specific information between the two primary motor cortices is predominantly mediated by excitatory mechanisms driven by the 'trained' M1 via at least two independent neural pathways. Key points: Participants were scanned during the untrained‐hand performance of a motor sequence, intensively trained a day earlier, and also a similarly constructed but novel, untrained sequence. The superior performance levels for the trained, compared to the untrained sequence, were associated with a greater magnitude of activity within the primary motor cortex (M1), bilaterally, for the trained sequence. The differential responses in the 'trained' M1, ipsilateral to the untrained hand, were positively correlated with experience‐related differences in the functional connectivity between the 'trained' M1 and (1) its homologue and (2) the dorsal premotor cortex (PMd) within the contralateral hemisphere. No significant correlation was evident between experience‐related differences in M1 – M1 and M1 – PMd connectivity measures. These results suggest that the transfer of sequence‐specific information between the two primary motor cortices is predominantly mediated by excitatory mechanisms driven by the 'trained' M1 via two independent neural pathways.